Aleitamento materno em crianças menores de um ano e sua relação com a segurança alimentar e nutricional - Santos, Gracielle Malheiro dos (2012)
This research addressed to evaluate the association between breast-feeding duration among children under one year and concerning alimentary and nutritional safety's situation in the households in which they reside. In 2005, a cross-sectional study it was conducted in 14 municipalities in Paraiba State was undertaken, in which 301 families were interviewed who had children less than one year. A structured questionnaire on socioeconomic, housing, infantile and maternal health, children's alimentary practices, breastfeeding and Brazilian Food Insecurity Scale was applied. The median durations of exclusive and total breastfeeding were calculated by Kaplan-Meier survival technique. The log-rank test was used in order to compare the times of lactation according to safety's situation and the levels of alimentary and nutritional insecurity. The variables were included in a multivariate Cox regression model according to Wald statistic to calculate the hazard ratio. Statistical analysis was carried out using the Statistical Package for the Social Sciences (SPSS) software, version 15. The average age was 5.8 months (95% CI: 5.4 6.2) among the studied children, of which 57.7% were female and 58.7% were declared multiethnic mulatto/ black color. Most mothers or custodians presented low socioeconomic status and housing, and those living in rural areas had the worst condition. Among the appraised children's mothers it was verified a great number of pregnancies and offspring, as well as high frequency of cesarean sections. During pregnancy, most mothers received counseling for breast-feeding (86.6%). According to the mothers, features that really support with breast-feeding were their proper nutrition, doing prenatal, spending more time with the baby and the father's understanding and support. Aspects considered drawback to breast- feeding were engorged breasts, breast inflammation, the mother being ill or to work outside. Water, fluid or powder milk and tea were the alimentary items offered with more frequency to the appraised children. Food security in families with children was of 50.8%, while food insecurity in mild, moderate and severe levels was 18.6%, 19.6% and 11.0%, respectively. According to the survival analysis the medium breast-feeding period lasted 32.4 days on exclusive breast-feeding (95% CI: 27.9 36.9) and 214 days in total breast-feeding (95% CI: 165.6 - 262). The median duration of exclusive breast-feeding according to the food security and insecurity (mild or moderate) was 30.4 days versus 61.8 days when family was in severe food insecurity (Log-Rank = 4.4; p = 0.036). Was significantly related to the duration of exclusive breast-feeding the access to garbage collection and severe food insecurity and gather information on breastfeed during prenatal. It was not possible to verify relationship with the studied variables and the total breast-feeding due to the high number of censorships. It can be concluded that the studied mothers remained longer exclusive breast-feeding which seems to be incorporated by households in most unfavorable situations of life, indicating that this behavior can be an alternative to maintain health and child survival in a situation of fragile life.